2023
DOI: 10.1101/2023.03.02.530853
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Expanding the molecular language of protein liquid-liquid phase separation

Abstract: Understanding the relationship between an amino acid sequence and its phase separation has important implications for analyzing cellular function, treating disease, and designing novel biomaterials. Several sequence features have been identified as drivers for protein liquid-liquid phase separation (LLPS), leading to the development of a “molecular grammar” for LLPS. In this work, we further probed how sequence modulates phase separation and the material properties of the resulting condensates. Specifically, w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
56
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 31 publications
(69 citation statements)
references
References 76 publications
13
56
0
Order By: Relevance
“…We found near-constant η values at sufficiently low shear rates for all sequences, indicative of their Newtonian liquid-like behavior, similar to that seen for experimentally characterized disordered protein condensates. 18, 24, 32 Similar to the MSD, η depended on the degree of charge segregation within the sequence. To illustrate this dependence, we considered the zero-shear viscosity η 0 of all sequences, which is obtained as an average of the η values from the Newtonian plateau observed at low shear rates ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We found near-constant η values at sufficiently low shear rates for all sequences, indicative of their Newtonian liquid-like behavior, similar to that seen for experimentally characterized disordered protein condensates. 18, 24, 32 Similar to the MSD, η depended on the degree of charge segregation within the sequence. To illustrate this dependence, we considered the zero-shear viscosity η 0 of all sequences, which is obtained as an average of the η values from the Newtonian plateau observed at low shear rates ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ask simply, to what extent is it possible for two IDRs to selectively assemble into distinct condensates with minimal co-mixing in the absence of shared ligands or macromolecules? Recently, our lab and others have revealed an amino acid code governing homotypic interactions that underlie liquid-liquid phase separation (LLPS) of various IDRs [18][19][20][21][22][23] . Coarse-grained models have provided insights on key residues or motifs that influence IDR saturation concentrations (C sat ) and client partitioning to condensed phases.…”
mentioning
confidence: 99%
“…Recently, our lab and others have revealed an amino acid code governing homotypic interactions that underlie liquid-liquid phase separation (LLPS) of various IDRs [18][19][20][21][22][23] . Coarse-grained models have provided insights on key residues or motifs that influence IDR saturation concentrations (C sat ) and client partitioning to condensed phases.…”
mentioning
confidence: 99%
“…In recent reports from our laboratories, Rekhi et al showed that decreasing the aromatic character of similar resilin-derived model artificial intrinsically disordered proteins (A-IDPs) capable of undergoing UCST behavior led to fewer interchain contacts in the protein condensates. 59 In the current studies, as indicated by their opacity, it is possible that a higher extent of interchain contacts and polymerization-induced phase separation (PIPS) 60,61 in bulk Y-4Ac hydrogels afforded them higher shear storage moduli compared to L-4Ac bulk hydrogels of the same composition (Figures S14−S16). Compared to a nonphase-separated hydrogel, local enrichment of the polypeptide likely results in formation of bicontinuous macronetworks comprising cross-linked bundles of polypeptide chains interconnected within a solvent-rich phase (Figure S17).…”
Section: W-rich Coacervates Act Asmentioning
confidence: 84%